2021
DOI: 10.3390/foods10010104
|View full text |Cite
|
Sign up to set email alerts
|

Upstream Regulator Analysis of Wooden Breast Myopathy Proteomics in Commercial Broilers and Comparison to Feed Efficiency Proteomics in Pedigree Male Broilers

Abstract: In an effort to understand the apparent trade-off between the continual push for growth performance and the recent emergence of muscle pathologies, shotgun proteomics was conducted on breast muscle obtained at ~8 weeks from commercial broilers with wooden breast (WB) myopathy and compared with that in pedigree male (PedM) broilers exhibiting high feed efficiency (FE). Comparison of the two proteomic datasets was facilitated using the overlay function of Ingenuity Pathway Analysis (IPA) (Qiagen, CA, USA). We fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Previously, a shotgun proteomics study, which was conducted with WS and WB co-affected muscles ( WS/WB ) collected at ∼5 min postmortem compared with normal muscles, showed potentially altered physiological mechanisms, including carbohydrate metabolism, protein synthesis, oxidative stress and mitochondrial dysfunctions ( Kuttappan et al, 2017 ; Bottje et al, 2021 ). When compared differentially abundant proteins of WS only muscle collected at 6 h postmortem (WS-6h) in this study with those in WS/WB muscles collected at ∼5 min postmortem (WS/WB-5min) in the previous study, proteins showing the same differential trends may reflect similar protein stabilities between WS and normal meat during processing procedures and short-term storage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, a shotgun proteomics study, which was conducted with WS and WB co-affected muscles ( WS/WB ) collected at ∼5 min postmortem compared with normal muscles, showed potentially altered physiological mechanisms, including carbohydrate metabolism, protein synthesis, oxidative stress and mitochondrial dysfunctions ( Kuttappan et al, 2017 ; Bottje et al, 2021 ). When compared differentially abundant proteins of WS only muscle collected at 6 h postmortem (WS-6h) in this study with those in WS/WB muscles collected at ∼5 min postmortem (WS/WB-5min) in the previous study, proteins showing the same differential trends may reflect similar protein stabilities between WS and normal meat during processing procedures and short-term storage.…”
Section: Resultsmentioning
confidence: 99%
“…Weighted gene co-expression network analysis ( WGCNA ) based on gene expression profiles obtained with WB and WS muscles suggested that alterations in extracellular matrix composition could activate the growth-related myopathies onset, and that collagen IV alterations may induce the endoplasmic reticulum stress response ( Bordini et al, 2021 ). Proteomics studies with severe WB and WS muscles identified differentially expressed proteins associated with increased protein synthesis, decreased carbohydrate metabolic activity, decreased mitochondrial biogenesis, and reduced function of rapamycin independent companion of mammalian target of rapamycin ( RICTOR ) ( Bottje et al, 2021 ; Kuttappan et al, 2017 ). However, global protein expression studies on WS-only muscle phenotype without other breast myopathy were limited in contrast to a variety of omics studies on WB (and WB with WS).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to glycolysis/gluconeogenesis and the protein-synthesizing pathways that were identified, mitochondrial activity has previously been reported to be among the most significant pathways influencing FE ( Bottje et al, 2002 ; Kong et al, 2016 ; Yang et al, 2020 ) and meat quality ( Abaht et al, 2019 ; Bottje et al, 2021 ). Mitochondria function is critical for improving FE due to its potential role in generating and utilizing energy extracted from feed ( Bottje et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Rather than adding myofibers, muscles grow longitudinally through the accretion of myoblasts, resulting in an increasing pool of myonuclei, which regulate the addition of sarcomeric units and skeletal muscle growth ( 44 , 45 ). Intense selection for growth performance in broilers causes an excessive rate of breast muscle growth ( 46 ), which may favor more vulnerable myofibers. After the occurrence of myofiber injury, monocytes invade and remove necrotic cells and cellular debris ( 47 ).…”
Section: Discussionmentioning
confidence: 99%